Вы находитесь на странице: 1из 25

:

. -.

.
. . . . (),
1907
.
. ,
ti, ti, ... , tk, ...
pij , tk+1 wj,
, tk wi.
.
,

(, . .).
. . .
. . 1930.
. ., ,
, ,
.

f(t, , ). f(t, , ) , ,
, t , y+dy.
( ), f(t, , )

2
f (t , x, y ) =
[ A( y ) f (t , x, y )] +
[ B ( y ) f (t , x, y )] ,5
dt
y
y 2


. . . A(y)
, ()
.
. . .


, ,
.
. . . ,
dt adt, a ,
;
. N
t = 0 Pn(t)
, t n . Pn(t)

dPn (t )
= NPn (t ) 1
dt
dPn (t )
= ( N n)Pn (t ) + ( N n + 1)Pn 1 (t ) ,2
dt

P0 (0) = 1, Pn (0) = 0
1
n N

Pn (t ) = C n N (1 e t ) n e ( N n )t 4
0, 1, 2, ..., N
, .
.
w1, w2, ..., wn, ... .
,
.
, wi
pij(t) , t wj,
.
pij(t) .
. .
.

- (-)

- - ,
( -)
, . . . 1906 M. (M. Smoluchowski) 1913 ; . (A.
Fokker) 1914 M. (M. Planck) 1917
,
-.
.- . . f (r, p,
t) p M
T

df
P df
d df

P
f
+

=
(
f + RT
)6
dr
dt
M
dr dp
p
M
p

U- . , -. , - . (J. Kirkwood)

1
KT

df

PF (t ) 7

F- (), <...> -
.
(1957,
.
- .
,
( )
. -.
, :

k ( k=1,2,3..) p,
p-1 . ( p 1/2 - ).
h. (x,t) - t x,

m , n-m .

: 0 h 0 t

-.
:

(1)
t:

,
x + t :

n .

0, h 0 :

- 2- .
, :

(2)
(x,t) - , -,
. (x,t) C(x,t) . .2
.
- ,
, .. .
c
. (2)
- (1).
F,
= BF (B ) :

(3)
:

(4)
-:

(5)
(4) (5) , B .

A :

() ,

, . ,


, .
, ,
-
, .

- .
-
0 f (x, t)
.
6.11) :

EP ( x, t ) =
S ' ( x, t )
x k

E , 6.11),
t

Fki(,',t) Fki ( x, x ' ; t ) = dt ' Bki ( x, x ' ; t )


0

S'(x,t) ,
0- 0 6.11).
, / , ,
,
6.1) ,
-.
.
, ,
6.1), ,
, .
, -
f (x, t) 6.1)
6.4).

0 f(x,t) .

(f(x,t)R[t;f(x',)})
,
f(x,t) 6.4).
-
() ,
() -
,

,
.


- 6.11)
6.15)
,
.
,

.
-, . , ,
- , ,
.

,
,
.
6.4.1. .
- (t):
d
x(t ) = Ax (t ) + f (t ), x (t 0 ) = x 0 6.31)
dt
. ,
. fi (t)
, , . .
f i (t ) f i (t ' ) = 2 Bij (t t ' )
t

( t t ) A
( t t ) A
6.31) : x (t ) = e 0 x 0 + de 0 f ( ) ,
t0

, x(t)
( t t ) A
( , ): x(t ) = e 0 x 0

ij2 (t , t ' ) = xi (t ) xi (t ) x j (t ' ) x j (t ' )

] = d{e
t

( t t 0 ) A

Be ( t t0 ) A

t0

6.32)

ij

, ,
6.32) -
p(x,t | x0,to),
6.31):
(

+
Aik x k ) p ( x, t x 0 , t 0 ) =
Bik
p ( x, t x 0 , t 0 )
t x
xi
x k

, 6.33)
.
F.31) ,
.
(, ),
.
.

d
(t ) = z (t ), (0) = 0
dt

z(t) -

z (t ) = 0, z (t ) z (t ' ) = 2 2 0 (t t ' )
t

(t ) = dz ( )
0

(t ) = 0, (t )(t ' ) = 2 2 0 min( t , t ' )


, ,
t
t
t

[t ; v( )] = exp i d ( )v ( ) = exp 2 0 d 1 d 2 v( 1 )v( 2 ) min( 1 2 )


0
0
0

, w(t) (t1, t2)


t2

(t1 ; t 2 ) = (t 2 ) (t1 ) = dz ( )
t1

w(t),

(t1 ; t 2 ) =0, (t1 ; t 2 )

=220 t 2 t1

w(t)
. ,
(t1;t2) (t3;t4) w(t)
.

(t 0 ; t 0 + t ) =

t 0 +t

dz ( )

t0

w(t). ,
w(t) w(to;to + t)
to. ,
, ,
. w(t) w(t), ,
,
.

. ( > 1)
w(at)
a1/2w(t).

w(t) t
w(at)/a1/2, .
,

w(t;) = t + w(t), > 0.


w(t;) , P(w,t;) =
( (w(t;)-w)} -:

2
+
) P(, t ; ) = D
P (, t ; ), P(,0; ) = ()
t

D =2 0. :
P (, t ; ) =

( + t ) 2
exp

4 Dt
2 Dt

,
, w(t;) < w,

F (, t ; ) =

dP(, t;) = ( 2

( z ) =

t
+
)
2D
Dt

6.37)

y2
dy
exp

2
2
1

F.35), ,
P (, t ; )

=h

= 0(t > 0) 6.39)

w(t;)
h. 6.35), 6.39), P(w,t;,h),
w < h
w(t;), t, ..
h. ,
, , t <t*, t*
h

w(t;) h:

dP(, t ;, h) = P(t < t*)

6.40


h:
h

F (t ; , h) = P (t* < t ) = 1 P (t < t*) = 1 dP (, t ; , h) 6.41

P (t ; , h) =

F (t ; , h) =
P (, t ; , h)
t

=h

> 0, w(t;) t h
t oo, P(t < t*) 6.40) ,
w(t;) h.
h

t lim

dP(, t ;, h) = P(

max

( ) < h)

6.42)

max ( ) = max (t , )
t( 0 , )

h. , 6.42) ,
max ()

F (h, ) = P (max () < h) = lim

dP(, t;, h)

6.43)

6.35), 6.39), , ,
P (, t ; , h) =

1
2 Dt

{exp[

( + t ) 2
h ( 2h + t ) 2
] exp[

]} 6.44)
4 Dt
D
4 Dt

: 6.41), t*
w(t,) h:
P (t ; , h) =

1
2 Dt Dt

exp[

( h + t ) 2
]
4 Dt

, 6.44) w t , , 6.43),

wmax() w(t;) [51, 160]
F ( h, ) = P (max ( ) < h) = 1 exp[

h
]
D

6.45)

,
:
P ( h, ) = ( (max ( ) h)) =

h
exp

D
D


,
.
()
, .
.

t

y (t , ) = e ( t , ) = exp( t + dz ( )) 6.46)
0

z()
<z(t)>= 0, (z(t)z(t')) = 220(t-t').

d
y (t ; ) = { + z (t )t (t ; )} ,
dt

y(0;)=1

P ( y, t ; ) = (e ( t ,) y ) =

1
P (, t ; )
y

=ln y

P(w,t;)
, 6.36), , ,
P ( y , t ; ) =

1
2 y Dt

exp{

(ln y +t ) 2
1
ln 2 ( ye t )
}=
exp(
) 6.47)
4 Dt
4 Dt
2 y Dt

D = 20-.
6.47) /D = 1
= Dt = 0.1 1 . 3.1.



=1,
y(t;a) .
, , 6.37), 6.38),

F ( y , t ; ) = P ( y (t ; ) < y ) = (

ln( ye t )
2 Dt

) 6.48)

y(t;),
y(t;a)
(0,). : 1.

,
y(t;) 1
[51, 160]
y*(t;a) = e-t.

6.49)

2. y(t;) ,
6.47)
-:
(

+
y ) P ( y , t ; ) = D
y
P ( y , t ; ), P ( y ,0; ) = ( y 1) 6.50)
t
y
y y

6.50)
y(t;),
y n (t ; ) = e n ( n / D ) Dt ,

1
y n (t ; )

= e n ( n + / D ) Dt n=1,2

6.51)

. ,
y(t;)
y*(t;) , .
/D = 1 y(t;D)
. , ,
< 1 Dt1, 6.48),
:
P ( y (l , D ) < 1) = (

Dt
1
) =1
e Dt / 4
2
Dt

. .
(y(t; D)} = 1,
y(t;D), , .
,
y(t;) .
3. y(t;)
- Mp(t, ),
[51, 160].
Mp(t, a), t
y(t;) < Mp(t,), ..
P{y(t;) < Mp(t,) t (0,oo)} = p.
6.45)
w(t;)
. , ,
wmax(P) w(t;)
, 0 < < ,
w(t;) < h Ln A, . , ,
y(t;)
{t,,) = (-)t 6.52)
6.45), , y(t;)
6.52), :
p=1-A/D
, ,

M p (t , , ) =

1
e ( )t 6.53
(1 p ) D /

, ,
(y(t;D)) = 1
y(t;D),
6.53),
y(t;D) < 1. , ,
= 1/2

y(t]D)<M1/2(t,D,D/2) = 4e-Dt/2 6.54)


t (0,).
y(t;D) 6.54) .
3.2.

,
y(t;D)
, .
,
. , y(t;),
,
,
, .. y(t;a) .
4.

y{t;):
t

S n (t ; ) = dy n ( ; )

6.55)


d
S n (t ; ) = y n (t ; ), S n (0; ) = 0
dt

d
y (t ; ) = { + z (t )} y (t ; ), y (0; ) = 1 6.56)
dt
, , {y(t;),Sn(t;)}
,

P ( S n , y, t ; ) = ( ( S n (t ; ) S n ) ( y (t ; ) y ))

, ,
-:
(

+ yn

y ) P ( S n , y , t ; ) = D
y
yP ( S n , y , t ; ), P ( S n , y ,0; ) = ( S n ) ( y 1)
t
S n
y
y y

6.57)
, F.57) , , ,
Sn(t;).

Sn(t;), .. ,
[51, 160].
6.55) :

, Sn(t;)

t

S n (t ; ) = dtxp ( n(t ) + n d1 z ( +1 )) 6.58)


6.58) ,
:
d
S n (t ; ) = 1 n( z (t )) S n (t ; ), S n (0; ) = 0
dt

P(Sn,t;) = ((Sn(t;) Sn)} :
(

+ yn
n
S n ) P ( S n , t ; ) = n 2 D
Sn
S n P ( S n , y, t ; ) 6.59)
t
S n
S n
S n
S n

6.59) ,

n
S n ( ) = dy ( ; ) :
0

P( S n ; ) =

1
2

(n D)

/ nD

)S

1+ / D
n

exp( 1

n 2 DS n

(z) -. , = 1

S ( ) = S1 ( ) = de( ; )
0

P( S ; ) =
( D)

n/D

)S

1+ / D

exp( 1

DS

6.60)

= D,
:

P( S ; D) =

1
1
exp( 1
), F ( S ; D ) = exp(
) 6.61)
2
DS
DS
DS


y(t;)

S (t ; ) = dy ( ; ) 6.62) t.
t

6.62)

S (t ; ) = y (t ; ) d exp( + d1 z (1 + t ))

6.63)

y(t;) 6.63) ,
6.63),
z() , ,
,
S(). ,
S (t ; ) P ( S , t ; ) = ( S (t ; ) S )

0 0

P ( S , t ; ) = dydS ( yS S ) P ( y , t ; ) =

dy
P ( y; t ; ) P ( S , y; ) 6.64)
y

(y,t;)
y(t;), 6.47), a P(S/y;)
6.60).

S

F ( S , t ; ) = P ( P ( S , t ; ) < S ) = dS P ( S , t ; )
0

F ( S , t ; ) = dyP ( y , t ; )F ( S / y; ) F(S;)
0

S(t;).
, = D, 6.47) F661),

F ( S , t ; ) =

dy
Ln 2 ( ye Dt )
y
exp(

4 Dt
DS
2 Dt 0 y
1

S(t;) < S Dt
DS.

Dt,
y(t;),
.

.
- ,
. , ,
Fkl(x,x;t) 6.11) ,
.
,
L =

2
Fki ( x, x; t ) . ,
x k xi

L =
F ( x 2 1)
x

,
.
-

F ( ) = dxf ( x) P1 / 2+i ( x)( > 0) 6.65)


1

-1/2+i() ,
d
d
1
( x 2 1)
P1 / 2 +i ( x) = ( 2 + ) P1 / 2 +i ( x ) 6.66)
dx
dx
4

6.65)

f ( x) = dtan( )F ( ) P1 / 2 +i ( x )(1 x ) 6.67)


0

F() 6.65).
,
-
L =

2
x

x
x

F ( ) = dxf ( x)K i ( x)( > 0)


0

Ki(x) ,

/2

1+-

2+2 ] Kix(x) =0,

dx dx >

F.68)

f(x) = J_ [ dx smh(Kx)F(x)Kix(x). F.69)


J

- (
1) :

p ( x, t x 0 , t 0 ) = D
( x 2 1)
p ( x, t x 0 , t 0 )
t
x
x
p ( x, t 0 x 0 , t 0 ) =( x x 0 )

p (t , ) = dxp ( x, t x 0 , t 0 ) P1 / 2 +i ( x )
1

6.70) P-1/2+i(x) x 1
(),

p (t , ) = D dxP 1 / 2+i ( x)
( x 2 1)
p ( x, t x 0 , t 0 ) 6.71)
t
x
x
1

p (t 0 , ) = P1 / 2 +i ( x 0 ) 6.72)

6.71)
P-1/2+i(x) 6.66),
(t,):

p (t , ) = D ( 2 +1 / 4) p (t , )
t

6.72)

p (t , ) = P1 / 2+i ( x0 )e D (

+1 / 4 )( t t 0 )

6.67),
6.70) - :

p ( x, t x 0 , t 0 ) = dtanh( )e

1
D ( 2 + )( t t 0 )
4

P1 / 2+i ( x ) P1 / 2+i ( x 0 ) 6.73)

to = 0 x0 = 1, 0

P ( x, t ) = dtanh( )e

1
D ( 2 + )( t t 0 )
4

P1 / 2 +i ( x) 6.74)

- 6.70)

P(x,0)=(x-1)

-.
-
,
. ,
, ,
,
. , ,
t >
-.
,
- . , -,
, -,
. .
.

d
x (t ) = f ( x ) + z (t ) g ( x ), x (0) = x 0 6.75)
dt

, , z(t) - (z(t))=0, (z(t)z(t))=2D(t-t) (D=20)


- :
(

+
f ( x)) P ( x, t ) = D
g ( x)
g ( x ) P ( x, t ; )
t x
x
x

(x), ,
f ( x )) P ( x) = Dg ( x )

d
g ( x ) P ( x, )
dx

( , () , .. <
< ()), :
P( x) =

C
1
f ( x)
exp(
dx 2
) 6.78)

{ g ( x)}
D
g ( x)

dxP ( x) =1

6.21) (f(x) = x, g(x) = 1)


6.78) :
P( x) =

2
exp(
x )
2D
2D

.
,
, :
d

ri (t ) =
H ({ri }, { p i })
dt
p i
d

pi (t ) =
H ({ ri }, { pi }) p i + f i (t ) 6.80)
dt
ri

i = l,2,...,N, H ({ ri }, { p i } ) =

pi2
+ U (r1 ,..., rN )
2

(), fi(t)
-

f i (t ) f j (t ' ) = 2 Dij (t t ' ) 6.81)

.
6.80) N
. -
6.80) :
2
N
N
N

{ p k P} = D 2 P({ ri }, { pi }, t ) 6.82)
P({ ri }, { p i }, t ) + { H , P}
t
k =1
k =1 p k
k =1 p k
(k )

{, } k =

k- .
p k rk
p k rk

, 6.82)
:
P ({ ri }, { p i }) = CExp (

H ({ ri }, { pi }) 6.83)



.
6.83) ,
,
. U(ri,... ,n) = 0
6.79).

6.83)
(),
:
P ({ ri }) = CExp (

U ({ ri }) 6.84)


6.83) .
(
),
(
).
, 6.80) :
d
1
1
ri (t ) =
U ({ ri }) + f i (t )
dt
ri

1 N U ({ ri } )
D
P ({ ri }, t ) =
(
P ({ ri }, t )) + 2
t
k =1 rk
rk

2
P ({ ri }, t ) 6.85)

2
k =1 rk
N

-.
- 6.82) 6.85)
. 6.80)

d
d

x(t ) = y (t ),
y (t ) = U ( x) y (t ) + f (t ) 6.86)
dt
dt
x

P ( x, y ) = CExp (

H ( x, y ), H ( x, y ) =

y2
+U ( x) 6.87)
2

. , 6.86)
,
.
, ,
,
d
v 0 (t ) = v12 (t ) v 0 (t ) + R + f (t )
dt

d
v1 (t ) = v 0 (t )v1 (t ) v1 (t ) 6.88)
dt
() ,
, ,
R, f(t).

R < 1, f(t) =

Vl = 0, vo = R

6.89)

vo(t)

d ~
~ (t ) + f (t ); (v
~ (t ) = v (t ) R ) 6.90)
v0 (t ) = v
0
0
0
dt
, R < 1
vo(t), 6.79), .
R > 1. f(t) = 0

v 0 =1; v1 = R 1 6.91)

~ (t ) .
vo(t) v0 (t ) =1 + v
0

6.88) :
d ~
~ (t ) + ( R 1) + f (t )
v0 (t ) = v12 (t ) v
0
dt

d
~ (t )v (t ) 6.92)
v1 (t ) = v
0
1
dt
^i(?) .
v1(0)> 0, v1(t) > 0. v1(t) : v1(t)=e(t)
6.92) 6.86):
d ~
U () ~
d
~ (t )
v0 (t ) =
v0 (t ) + f (t ),
(t ) = v
6.93)
0
dt

dt

U () =

1 2
e ( R 1)
2

(t) , vo{t)
. . 3.3
U(0)). U(0)=1/2(R-1)(1-ln(R-1))
0 = ln
v1 =

R 1 ,

R 1 . ,

(t) vo(t) 6.87):

P(v~0 , ) = C exp H (v~0 , )


D

6.94)
2
~
v0
~
H ( v 0 , ) =
+ U ()
2

6.94) , R > 1
vo(t) 6.88) :

P (v 0 ) =

(v 0 1) 2
exp(
) 6.95)
2D
2D
1

(t) ,
. v1(t),

P (v1 ) = constv

R 1
1
D
1

exp(

(v1 ) 2
) 6.95)
2D

(R = 1), 6.95),
V1(t). ,
,
v1(t),
.
v1(t) .

.
1990- . -
, . , . . ;
- ( . .
). -
(
)
. , ,
-.
,
() - .
,
(. , .)

Оценить